Hubungan Keadilan dan Kepuasan dengan Keinginan Berpindah: Peran Komitmen Organisasional sebagai Variabel Pemediasi - Fahrudin Js Pareke (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2004)
The stream of the research on employee’ work behavior had been provided empirical evidences about the effect of one behavior on the others behavior. Current researches were conducted with two main concerns, first, to investigate the affect of distributive and procedural justice, and job satisfaction on turnover intent. And second, to examine the roles of affective, continuance and normative organizational commitment as the mediating variables on the effects of distributive, procedural justice, and job satisfaction on turnover intent. One-hundred-and-seventy-four employees from two state and private organizations located in Bengkulu Province participated voluntarily as the respondents. Three steps Mediated Regression Analysis (MRA) was employed to test the hy¬potheses. As expected, distributive justice, procedural justice, and job satisfaction negatively affect the turnover intent. In addition, the effect of distributive justice on turnover intent was mediated by affective and continuance organizational commitment. The effect of procedural justice was mediated by affective, continuance, and norma¬tive organizational commitment. And the effect of job satisfaction on turnover intent was mediated by affective and normative organizational commitment. The results were discussed as they related to researchers and practitio¬ners who becoming interested in employee’ work behavior.Key words: Distributive justice, procedural justice, job satisfaction, organizational commitment, turnover intent